Survival Pasien Kanker Kolorektal di RSUD Nganjuk dan Ekspresi Gen APC, KRAS dan SMAD4 Pada Tumornya - Pratika Yuhyi Hernanda; Pramugyono Pramugyono; Ida Septika Wulandari; Harman Agusaputra; Maria Wijayanti Sugeng; Fuad Ama; Nadia Fitri Shalsabillah (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: The survival of colorectal cancer patients is significantly influenced by comorbid factors, including age, smoking, obesity, comorbidities, and genetics. The purpose of this study was to analyze factors affecting colorectal cancer survival in Nganjuk Regional General Hospital and to examine the expression of the APC, KRAS, and SMAD4 genes in tumor tissue.Methods: We analyzed the comorbid factors in 51 colorectal cancer patients and then analyzed their relationship to colorectal cancer survival. Immunohistochemistry (IHC) staining was performed to examine the expression of the KRAS, APC, and SMAD4 genes in colorectal cancer tissue. Data were analyzed using bivariate analysis between variables using the Chi-square test, and survival analysis was performed using Kaplan-Meier statistical analysis.Results: The data shows that colorectal cancer patients with comorbidities tend to have a lower survival rate than those without comorbidities (P-value 0.054), and patients with metastases also have a lower survival rate (P-value 0.748). APC and SMAD4 gene expression in stromal tissue IHC was more dominant than KRAS gene expression in the stroma. Increased gene expression in the stroma indicates its role in tumor invasion and metastasis.Conclusion: Comorbidities and the presence of metastases negatively impact the survival rate of colorectal cancer patients. APC and SMAD4 gene expression in the stromal tissue was more dominant than KRAS gene expression in the stroma, suggesting a role for these genes in tumor invasion and metastasis.